Malay Reasoning - Mohd Zain, Shaharir (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2015)
We discuss the nature of Malay statements using the term moga-moga or its equivalents semoga and mudah-mudahan, especially when referring to an implication. We show that this term is uniquely Malay. In fact, even though it may be translated as â€œhopefullyâ€, â€œin hopeâ€, â€œmayâ€, â€œmay it beâ€, â€œwishâ€ and â€œletâ€, further analysis of its usage as we have shown here, these translations are found to be inaccurate. Therefore, we propose to anglicize the terms based on moga-moga so that we discuss here the mogamic reasoning and its relation with the well-known modal reasoning (modal logic), that is, the English modal reasoning. We show that the mogamic reasoning is different from the English modal reasoning. From the beginning of our discussion, we argue that our mogamic reasoning is suitable to include the other two Malay forms of reasoning, namely, the budic reasoning (based on the Malay proverbs and pantuns on budi) originally proposed by Lim (2003), Hassan (2003) and the Islamic reasoning, the insya Allah reasoning proposed by Shaharir (2013a); and simultaneously improve the concept of budic reasoning.